Studi Kualitatif Aspek Hukum Persetujuan Tindakan Medis (Informed Consent) Di Ruang Instalasi Gawat Darurat (IGD) Rumah Sakit - Anik Indriono (LPPM Universitas Pekalongan, 2022)
The hospital is a place to organize health service efforts, including promotive, preventive, curative, and rehabilitative; these health services are carried out through emergency installations, outpatient installations, and inpatient installations. The emergency room is a special service room that provides comprehensive and continuous services 24 hours a day for patients. Patients who enter the hospital emergency room certainly need fast and precise help, and for that reason, there needs to be a standard for providing emergency services so that patient disability and death can be prevented. The purpose of this study is to know the definition, legal basis, and legal consequences if informed consent is not implemented. The research method used is a normative juridical approach or normative legal research, namely legal research conducted by examining library materials or secondary data. The results showed that in an emergency situation, to save the patient's life and prevent disability, consent for medical treatment is not required, but the doctor must make a medical record regarding the actions taken and then explain after the patient is conscious. Hence, we can conclude that informed consent or an explanation of the approval of medical action to patients in the hospital must be carried out at the beginning before the action except in the emergency room. The implementation of informed consent in the emergency room cannot be done at the beginning because the main thing is to save lives first, but all actions must be recorded in the medical record and delivered to the patient after completion of the action when the patient is conscious.